2021
DOI: 10.1186/s12934-021-01625-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose induced protein 1 (Cip1) from Trichoderma reesei enhances the enzymatic hydrolysis of pretreated lignocellulose

Abstract: Background Trichoderma reesei is currently the main strain for the commercial production of cellulase. Cellulose induced protein 1 (Cip1) is one of the most abundant proteins in extracellular proteins of T. reesei. Reported literatures about Cip1 mainly focused on the regulation of Cip1 and its possible enzyme activities, but the effect of Cip1 on the enzymatic hydrolysis of lignocellulose and possible mechanism have not still been reported. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…It is known that accessory proteins, such as glucuronoyl esterase (Cip1 and Cip2), swollenin (Swo1), and AA9 lytic polysaccharide monooxygenases (LPMOs), play important roles in enhancing lignocellulose degradation [ 34 ]. Especially, Cip1 can reduce the non-productive adsorption of lignin by cellulase and Cip2 acts in the cleavage of hemicellulose-lignin crosslinks [ 35 , 36 ]. Ma et al demonstrated by RNA sequencing in T. reesei that Xyr1 could stimulate the expression of those accessory protein-encoding genes [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that accessory proteins, such as glucuronoyl esterase (Cip1 and Cip2), swollenin (Swo1), and AA9 lytic polysaccharide monooxygenases (LPMOs), play important roles in enhancing lignocellulose degradation [ 34 ]. Especially, Cip1 can reduce the non-productive adsorption of lignin by cellulase and Cip2 acts in the cleavage of hemicellulose-lignin crosslinks [ 35 , 36 ]. Ma et al demonstrated by RNA sequencing in T. reesei that Xyr1 could stimulate the expression of those accessory protein-encoding genes [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…49 Considering that cellulose is always embedded in the hemicellulose matrix mainly composed of xylan, increased xylanase and arabinofuranosidase activities would be anticipated to contribute to enhancing the overall efficiency of lignocellulose hydrolysis. On the other hand, the enhanced production of nonhydrolytic SWOI and CIPI that have been found to significantly promote the enzymatic hydrolysis of biomass materials 11,12 might also play important roles in contributing to the degradation of corn fiber.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Apart from (hemi)­cellulolytic enzymes, nonhydrolytic proteins, including swollenin (SWOI) and cellulose-induced proteins (CIPI and CIPII), have also been identified in T. reesei secretome. ,, These components have been shown to contribute to promoting lignocellulose hydrolysis. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the fermentation induction process, a low level of basal cellulase from T. reesei is always required to hydrolyse solid inducers to produce small molecules, which can then enter cells to induce cellulase production; therefore, the induction efficiency of solid inducers is unsatisfactory, and the fermentation of T. reesei with solid inducers has no application prospects. [6][7][8] For soluble inducers, the heat transfer efficiency in the fermenter is high, and energy consumption is low. Moreover, a higher induction efficiency can be achieved with soluble inducers because cellulase production can be directly induced in cells without the need for a basal cellulase level to degrade the inducer into small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, during the fermentation induction process, a low level of basal cellulase from T. reesei is always required to hydrolyse solid inducers to produce small molecules, which can then enter cells to induce cellulase production; therefore, the induction efficiency of solid inducers is unsatisfactory, and the fermentation of T. reesei with solid inducers has no application prospects. 6–8…”
Section: Introductionmentioning
confidence: 99%